The Factors That Attract Foreign Direct Investment in Mekong Sub-region Countries - PHENGMUANG, Viengphone; HER, Pheng; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to analyze the factors that attract foreign direct investment to the countries of the Mekong sub-region. For this purpose, World Bank panel data from 2000-2023 (24 years) are used. Variables include foreign direct investment (FDI), GDP per capita, trade openness, inflation rate and exchange rate. The Panel Autoregressive Distributed Lag (ARDL) model was implied. The analysis revealed that GDP per capita of the Mekong Sub-region countries has a positive impact on FDI at 0.01 level of statistical significance, as the size of GDP per capita can indicate the level of economic activity, which can attract investors interested in expanding their customer base or creating demand for goods and services in that economy. It also provides information about the income, purchasing power and consumption of the local population. At a statistical significance level of 0.01, trade openness is positively correlated with FDI. Greater trade openness increases the value of FDI, as trade liberalization increases the attractiveness of foreign investment by reducing restrictions and regulations related to the import and export of goods. Inflation in the countries of the Mekong sub-region has a negative impact on FDI at a statistical significance level of 0.01, as high inflation leads to economic uncertainty and reduces the purchasing power of the local currency (compared to the US dollar). It also increases the cost of goods, services and labor, and high-value business transactions reduce domestic consumption capacity and market opportunities, making investment less attractive. While the exchange rate is insignificant at any statistical significance level.